A theoretical development to simplify the analysis of rectangular patch microwave sensor built on multi-layer substrate - Wan Ali, Wan Khairuddin (2003)
This paper presents a method to simplify the analysis of a square patch microwave sensor built on a multi-layer substrate. The main feature of this method is the simplification of a multi-layer sensor structure into a sensor structure with a single homogeneous layer. The equivalent dieletric constant for the new single homogenous layer was discriminated using the method proposed in this paper. Effectively it eliminates the problem of mode matching between layers and thus reduces the amount of calculation and computing time. The method was compared with the experimental results and was found to give an error less than 4% in the worse case.